ANALISIS AKAR MASALAH KETIDAKEFEKTIFAN MANAJEMEN KELAS DI SEKOLAH DASAR DI SALATIGA DAN SEKITARNYA - Momongan, Hilda Saranita; Supramono, Supramono (Kelola: Jurnal Manajemen Pendidikan, 2015)
The aim of this study is to determine the root cause of ineffectiveness at classroom management which is applied by teachers as well as to propose solution to overcome ineffectiveness at elementary schoolâs classroom management. The data collection technique used in this research is focused group discussions and observations in the classrooms. The analysis technique used is Fishbone analysis or Ishikawa diagram. The results of this study shows that there are six roots of ineffectiveness problem at classroom management, namely: 1) teachers did not focus on students individually but to the curriculum only; 2) the existence of dissability students have different learning pace compared to others; 3) there was no demanding from principal about fun learning implementation in classroom; 4) teachers luck of knowledge about classroom management; 5) teachers lack to provide interpersonal relationship with students; 6) teachers had low trust about students ability to disciplined and organized themselves. The proposed solutions formulated together are such as teachers review the lesson plans and the daily teaching journal, teachers implement the system of reward and punishment as well as peer-teaching method to students, and principals require fun learning and supervise teachers in the classrooms.Â